KHAZANAH LEKSIKON KEPADIAN DALAM MASYARAKAT DAYAK KANAYATN BANANA’-AHE KABUPATEN LANDAK - Selpiana, Selpiana; Madeten, Sisilya Saman; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study provides views on rice related to tools for planting and harvesting rice or even knowing the part of rice in Sabaka Village, Mempawah Hulu District, Landak Regency. The problem in this study is how the lingual lexicon unit forms, the lexical meaning, the cultural, and the level of understanding the rice lexicon. The purpose of this study describes the lexicon of occurrence. The method used is descriptive and qualitative research forms. The source of this research data is the informant and the data in the form of lexicon of the treasures of the Dayak Kanayatn Banana'-Ahe community of Landak Regency. The techniques used are interviews and data collection tools are recorders, cameras, pens and notebooks. Based on the results of data analysis found one hundred six (106) lexicon data that consists of the number of parts of rice plants, animals and plants disturbing rice plants, the process of rice cultivation, objects related to rice, tools used in rice farming, soil types, types of rice, the material used for completing the custom of paddy farming, the actors who play a role, the time of implementation, the flow of rice into rice, the tools used for planting and harvesting rice.                                                                                     Keywords: treasure, rice, lexicon, and sense